Epidemiology of Dementia among people aged ≥ 65 years in Benin (West Africa) - (:unkn) unknown (My University, 2010)
The objective of this research is to expand our understanding on dementia, particularly to enrich its epidemiology and social aspects in order to enable health policy makers to develop an adequate policy for the management of dementia among older population in Benin.Methods : A transversal survey in the general population have helped to diagnose dementia among those aged ≥ 65 years and residing in the city of Cotonou and the rural district of Djidja for at least 5 years. Screening for potential dementia subjects was performed by using a Community Screening Instrument for Dementia (CSID). The clinical diagnosis was made by a neurologist by using DSM-IV criteria, and if possible or probable cases of Alzheimer's disease were identified by using National Institute for Neurological and Communicative Disorders and Stroke - Alzheimer's Disease and Related Disorders Association (NINCDS - ADRDA) criteria.Results : A total of 1139 individuals aged at least 65 years from Cotonou and 465 from rural Djidja were included. The females were 54.1% and mean age was 73.4± 7.2 years at Cotonou. In Djidja, females were 69.1% of the study population and mean age was 71.9± 5.0 years. The prevalence rates were 3.7 (95% CI: 2.6 - 4.8) in urban Cotonou and 2.6% (95%CI: 1.1 - 3.8) in rural Djidja. The prevalence among Cotonou Females was 2.6% (1.6 - 3.5) and among those at least 85 years was 12.8% (6.0 - 19.5). In Djidja, it was 3.4% (1.8 - 5.0) among females and 6.0% (2.8 - 11.1) among those at least 80 years. Alzheimer was the most dominant type in both zones. APOE allele ε4 was present in 22.2% of dementia individuals. Associated factors in urban zones were living alone (p= 0.02) and low weight (p= 0.01) and depression (p= 0.02). The communities in Benin were not aware of dementia as a disease but as a normal aging process.Conclusions : Prevalence of dementia in Benin is not very different as seen in other tropical countries of Africa, Asia and Latin America. It was howe
Keywords: African Research